Agricultural research organisations' role in the emergence of agricultural innovation systems. Issue 1 (2nd January 2017) - Hellin, Jon; Camacho, Carolina
ABSTRACT: Poor farmers seldom benefit from new agricultural technologies. In response, research and extension approaches based on agricultural innovation systems are popular. Often agricultural research organisations are the network brokers, facilitating the emergence of the innovation system. Based on an analysis of the Sustainable Modernization of Traditional Agriculture (MasAgro) initiative in Mexico, this viewpoint suggests that such organisations are more often suitable network brokers when the objective is the development and scaling out of a technology by itself. When the objectives are multi-faceted and include extension and education, other actors are better placed to be the network broker.